American sirens : the incredible story of the Black men who became America's first paramedics - Hazzard, Kevin, 1977- (Hachette Books, 2022)
"Up until 1968, if you suffered a medical crisis, your chances of survival were minimal. That all changed with the Freedom House EMS in Pittsburgh, a group of Black men who became America's first paramedics and set the gold standard for emergency medicine around the world, only to have their legacy erased-until now. Born from the vision of a Nobel Prize-nominated physician, the needs of a country in pain, and the ashes of Pittsburgh's downturn in the 1960s, Freedom House brought together a group of young, uneducated Black men to forge a new frontier in health care. Their job was grueling, the rules made up as they went along, and their mandate nearly impossible: prove to a skeptical public and the politicians that paramedics were a noble and valuable endeavor and, most importantly, that they themselves were worthy professionals performing a crucial public service. Despite the long odds and attempts to shut them down, they succeeded spectacularly. In American Sirens, acclaimed journalist and paramedic Kevin Hazzard tells a dramatic story of heroes and villains, of brutal attempts to stifle hope, and the resilience of a community that fought back. He follows a rich cast of characters that includes John Moon, an orphan who found his calling as a paramedic; Peter Safar, the Nobel Prize-nominated physician who invented CPR and realized his vision for a trained ambulance service; and Nancy Caroline, the idealistic young doctor young doctor who turned a scrappy team into an international leader. At every turn they battled racism-from the community, the police, and the government. Never-before revealed in full, this is a rich and troubling hidden history of the Black origins of America's paramedics, a special band of dedicated essential workers, who stand ready to serve day and night on the line between life and death for every one of us"--